2012
DOI: 10.1038/nature11260
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction accelerates atherosclerosis

Abstract: SUMMARY During progression of atherosclerosis, myeloid cells destabilize lipid-rich plaque in the arterial wall and cause its rupture, thus triggering myocardial infarction and stroke. Survivors of acute coronary syndromes have a high risk of recurrent events for unknown reasons. Here we show that the systemic response to ischemic injury aggravates chronic atherosclerosis. After myocardial infarction or stroke, apoE−/− mice developed larger atherosclerotic lesions with a more advanced morphology. This disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
843
6
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 919 publications
(907 citation statements)
references
References 36 publications
39
843
6
5
Order By: Relevance
“…We did not find indications of fibrous cap thinning after orthopedic surgery, which besides necrotic core expansion is another hallmark of vulnerable, inflammatory plaque 8,22 . We M A N U S C R I P T…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…We did not find indications of fibrous cap thinning after orthopedic surgery, which besides necrotic core expansion is another hallmark of vulnerable, inflammatory plaque 8,22 . We M A N U S C R I P T…”
Section: Discussioncontrasting
confidence: 62%
“…ApoE-/-mice demonstrated that the systemic inflammatory response to myocardial infarction aggravates chronic atherosclerosis 22 . Together with the results described herein, these studies support an important role for systemic inflammation in plaque destabilization and might thereby contribute to increased risk of cardiovascular events.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of cardiovascular events is particularly high in patients with earlier CVD manifestations 6, 7. For example, the 3‐year cumulative incidence of major adverse cardiovascular events in patients undergoing carotid endarterectomy was 13% 8.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to events within the brain, lymphocytes, neutrophils, and monocytes traffic to the brain from the periphery and contribute to further neuronal damage. The spleen is a principal reservoir that reduces in size after stroke, releasing inflammatory cells and cytokines into the circulation [8][9][10][11][12][13][14][15]. In addition, the bone marrow mobilizes a subpopulation of multipotent stem cells into the peripheral blood following stroke, which is then directed towards the brain, as well as peripheral organs such as the spleen [16].…”
Section: Central and Peripheral Mechanisms Of Inflammationmentioning
confidence: 99%